Temporal trends in management and outcome of patients with acute coronary syndrome according to admission low-density lipoprotein cholesterol levels. Issue 7 (November 2020) - Shuvy, Mony; Peretz, Alona; Gotsman, Israel; Vorobeichik, Dina; Shlomo, Nir; Minha, Saar; Pereg, David
Abstract : Background: The importance of differences in baseline low-density lipoprotein cholesterol (LDL-C) levels and pretreatment with statins on the temporal improvement in outcome of acute coronary syndrome (ACS) patients has not been studied yet. Methods: Patients were divided into two groups according to baseline LDL-C levels: LDL-C <130 mg/dl and LDL-C ≥130 mg/dl. Baseline characteristics, clinical data and outcomes were compared for each LDL-C group between patients enrolled in early (2000–2006), mid (2008–2010) and recent (2013–2016) surveys. Results: The study population was comprised of 8343 patients. Patients with LDL-C <130 mg/dl were older and were more commonly pretreated with aspirin and statins compared to patients with LDL-C ≥130 mg/dl. Patients included in recent surveys were more frequently selected for an invasive strategy with coronary angiography and subsequent revascularization, and were more commonly treated with guideline-based medical therapy. For patients with a LDL-C ≥130 mg/dl, the temporal improvements in therapy were associated with lower 1-year mortality rates (7.2, 4.4 and 3.5% for patients in early, mid and late surveys, respectively, P = 0.006). That temporal improvement in outcomes existed only in statin-naïve patients. For patients with LDL-C <130 mg/dl, temporal improvement in treatment was not accompanied by a reduction in 30 day or 1-year mortality rates. Conclusion: Treatment of ACS patients has improved over the past decades regardless of LDL-C levels. This improvement was accompanied by lower mortality rates in ACS patients with LDL-C ≥130 mg/dl, but not in patients with LDL-C <130 mg/dl.